Microsoft Visual Basic .NET programmer's cookbook - MacDonald, Matthew (Microsoft Press, 2003)
Filled with the ingredients developers need-code samples, instructions, and solutions to common problems-this book is the logical place for developers to start building projects and learning more about Visual Basic .NET.